Increasing the Students’ Ability in Reading Comprehension by Using Two Stay Two Stray (TSTS) Strategy at the Eighth Grade of SMP Negeri 3 Gunungsitoli Selatan in 2023/2024 - Jernih Tinince Orbarita; Riswan Zega (RETORIKA: Jurnal Ilmu Bahasa, 2024)
Reading is a process that starts with word recognition, progresses to comprehension, and involves the reader and the text negotiating meaning. The aim of the study was to improve the reading comprehension skills of eighth-grade students at SMP Negeri 3 Gunungsitoli Selatan in 2023–2024 by implementing the Two Stay Two Stray (TSTS) program. Two Stay Two Stray is the strategy that give opportunities for students to share the information with other learning groups in classroom activities. Some students of the eighth grade could not comprehend the particular descriptive text in the form of identifing the generic structure of reading comprehension especially in descriptive text, and the students were unable to understand the language features of reading comprehension especially descriptive text.In this research, Classroom Action Research (CAR) were applied by the researcher, that has devided into two cycles and two meetings for each. In the first cycle the students skills in reading comprehension were not satisfying due to the students level of “very fail and less level” moreover, the teaching enviromentalin learning process under the ideal condition, in cycle two the condition of teaching learning process were very good, so the result is satisfying. Scores ranged from 65 to 85, with 85 being the highest possible. Furthermore, the lowest possible score was 65 while the average for students in Cycle II was 85. Moreover, Cycle II students' average score was 72.The Two Stay Two Stray Strategy can improve pupils' reading comprehension skills, according on the researcher's analysis of the research findings.